2016
DOI: 10.1097/olq.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Social Marketing Campaign on HIV and Sexually Transmissible Infection Testing Among Men Who Have Sex With Men in Australia

Abstract: Increasing HIV/STI testing trends among MSM occurred pre- and post-DDU, coinciding with other plausible drivers of testing. Modest changes in HIV testing post-DDU suggest that structural changes to improve testing access may need to occur alongside health promotion to increase testing frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…A substantially smaller number of people, particularly among first-time testers, accessed RAPID after seeing an advertisement on a dating app. These results highlight the importance of a strong on-line presence, but consistent with broader evidence, suggest limited value in relying on advertising through dating apps as a way to increase testing uptake [37, 38]. …”
Section: Discussionsupporting
confidence: 63%
“…A substantially smaller number of people, particularly among first-time testers, accessed RAPID after seeing an advertisement on a dating app. These results highlight the importance of a strong on-line presence, but consistent with broader evidence, suggest limited value in relying on advertising through dating apps as a way to increase testing uptake [37, 38]. …”
Section: Discussionsupporting
confidence: 63%
“…A summary of the article collection process is presented in the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) Flow Diagram in Figure . A total of 27 articles were excluded because the mean sample age was ≥30 years .…”
Section: Resultsmentioning
confidence: 99%
“…technical reports in the grey literature; non‐English peer‐reviewed publications) are not accounted for in our review. Third, because our inclusion criteria required a sample of at least 50% gbMSM under 30 years of age, studies that may have reported relevant findings about online intervention with gbMSM are excluded ; future analyses of these studies will provide important details about the experiences of older generations of gbMSM with online interventions. Nevertheless, these findings provide a key “first step” in informing both potentially effective strategies and a renewed research agenda regarding the development of evidence‐based online interventions to address HIV/STBBIs among young gbMSM.…”
Section: Discussionmentioning
confidence: 99%
“…Of 72 unique publications identified in our original search, 14 studies [1819, 20*, 21*, 22*, 23*, 24*, 25*, 26*, 27*, 28*, 29, 30**, 31**,32*] met the inclusion criteria and were published between April 2015 and March 2017 (Table 1). Inclusion criteria included articles in English that reported data on impact of online interventions in increasing access to HIV and sexually transmitted infections (STIs) related information, reaching and engaging online key populations in HIV/STIs awareness and/or demonstrating testing and prevention services uptake.…”
Section: Online-to-offline (O2o) Modelsmentioning
confidence: 99%
“…Large-scale, time-based and hyperlocal social media based advertising, and crowdsourcing campaigns are such an example. Increasing HIV/STI testing trends among MSM pre- and post- a social marketing campaign have been reported in Australia [20*]. The 16-week ‘Tu Amigo Pepe’ campaign led to a significant and immediate impact on HIV testing rates among young Latino immigrant MSM [21*].…”
Section: Types Of O2o Models In Hiv Service Deliverymentioning
confidence: 99%